Proteomic snapshot of spearmint (Mentha spicata L.) leaf trichomes: A genuine terpenoid factory. Issue 22 (November 2013) - Champagne, Antoine; Boutry, Marc
<x xml:space="preserve">Abstract</x> Peltate glandular trichomes from Mentha spicata were purified on a Percoll gradient and soluble and membrane proteins were trypsinized and the peptides were separated by nano‐LC fractionation and analyzed by MALDI‐MS/MS. The vast majority of the 1666 proteins identified were housekeeping proteins or involved in the primary metabolism. However, 57 were predicted to be involved in the secondary metabolism. Of these, 21 were involved in the synthesis of phenylpropanoids and phenolics and 32 in terpenoid synthesis. Of the 14 membrane transporters identified, the 11 ATP‐binding cassette transporters provide good material for assessing whether active transport is required for the transfer of monoterpenoid intermediates between cellular compartments and for the secretion of the final products into the subcuticular storage cavity. In conclusion, this proteome analysis of M. spicata peltate trichomes has identified several candidate proteins that might be involved in terpenoid synthesis and transport. The data have been deposited to the ProteomeXchange with identifier PXD000352 (http://proteomecentral.proteomexchange.org/dataset/PXD000352).